Anatomical observations of the testicular veins - Piffer, C. R.; Piffer, M. I.S. (My University, 1988)
The medico-surgeon interest in relation to testicular veins, lead the author to realize anatomical observations of the right and left testicular veins in 40 cadavers, with the purpose to verify the number of veins to each other antimere, the variability in its modes of termination, the angles that form at the confluency levels, as well as the presence and the number of ostials and parietals venous valves. The obtained founds by the authors, are considerated extremely valid and helpfull to the specialists of the medical area, when of realization of testicular phlebography. The varicocele appearance in these veins was motive of discussion by the authors too.